ChemInform Abstract: Elucidating Silk Structure Using Solid‐State NMR. Issue 7 (18th February 2014) - Asakura, Tetsuo; Suzuki, Yu; Nakazawa, Yasumoto; Holland, Gregory P.; Yarger, Jeffery L.
Abstract Review: 104 refs.